Characteristics of Shell Bone as an Identification Tool for Turtle Species (Reptiles: Testudines) in Java, Borneo, and Sumatra - Donan Satria Yudha; Fidelis Triki Sadewa Aritona; Rury Eprilurahman (Journal of Tropical Biodiversity and Biotechnology, 2020)
There are 42 species of turtles; including sea turtle, freshwater turtle, tortoise, and softshell turtle (Reptilia: Testudines) living in Indonesia today. Turtles have economic values for quite a long time and it has led to illegal trade such as smuggling of carapace and plastron bones. Identification is needed to find out more details about the turtle species. Turtles have shells as unique features with different characteristics on each species. Shell’s identification usually relies on the shape of carapace and plastron. The purpose of this research is to understand turtle shell morphological characters and determine the diagnostic characters of each species. We conducted visual observation on specimen collections from the Laboratory of Animal Systematics, Faculty of Biology, Universitas Gadjah Mada and Museum of Biology, Faculty of Biology, Universitas Gadjah Mada. The result shows that each turtle species have their own unique shell bone’s characters, therefore it can be used to determine each turtle species of Indonesia.